Muscular activation differences between professional and amateur soccer players during countermovement jump - Abdullah Soylu; Ali Cerrah; Elvin Onarıcı Gungor; Hayri Ertan (Selcuk University, 2014)
The purpose of this study was to compare the muscular activation strategies of professional and amateur soccer players during countermovement jump. Twenty male soccer players, consisting of 10 amateurs (age: 22.9±3.1 year, training status: 12.2±3.1 year) and 10 professionals (age: 22.2±2.5year, training status: 13.7±2.7year) volunteered to participate in the study. Dominant leg surface electromyography activities of five muscles were recorded during countermovement jump. In addition, isokinetic strength of knee flexor and extensors, peak and average power were calculated. According to our results, the average countermovement jump heights were calculated for amateurs (37.1±3.12 cm) and professionals (41.3±2.58 cm). Furthermore, gastrocnemius muscle activation occurred significantly higher in professional soccer players than that of the amateur soccer players during propulsion (between -150ms and -120ms) and flight phase (between 150ms and 270ms) (p lt;0,05). Rectus femoris, vastus lateralis, vastus medialis and biceps femoris muscles contraction values were almost similar in both amateur and professional soccer players which their age, training year and muscle strengths are similar. It could be concluded that pre-activation and post landing phase are important for the jumping performance for both groups; however; the high activation of gastrocnemious muscle could be one of the important determinant for the superior jump performance